2010
DOI: 10.1007/s11010-010-0444-3
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of high sensitivity C-reactive protein by soluble receptor for advanced glycation end products

Abstract: High sensitivity C-reactive protein (hs-CRP) is synthesized mainly by hepatocytes in response to tumor necrosis factor-alpha (TNF-alpha), interleukin-1 (IL-1), and interleukin-6 (IL-6). The interaction of advanced glycation end products (AGEs) with the receptor for advanced glycation end products (RAGE) increases the expression of the cytokines TNF-alpha, IL-1, and IL-6. Soluble receptor for advanced glycation end products (sRAGE) competes with RAGE for binding with AGEs. Hence, low sRAGE levels may increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…12 Similar to this study, in both HbA1c <6.5% and ≥6.5% groups of current study, there was a negative correlation between sRAGE and hsCRP. Previous studies have documented inverse correlations between sRAGE with CRP 13 and low levels of sRAGE among persons with coronary heart disease 14 . sRAGE can serve as a 'bait' receptor to catch ligand and able to inhibit the cellular signaling.…”
Section: Discussionmentioning
confidence: 95%
“…12 Similar to this study, in both HbA1c <6.5% and ≥6.5% groups of current study, there was a negative correlation between sRAGE and hsCRP. Previous studies have documented inverse correlations between sRAGE with CRP 13 and low levels of sRAGE among persons with coronary heart disease 14 . sRAGE can serve as a 'bait' receptor to catch ligand and able to inhibit the cellular signaling.…”
Section: Discussionmentioning
confidence: 95%
“…Interaction of AGE with RAGE leads to increased expressions of inflammatory cytokines such as TNF-␣, IL-1, and IL-6 through nuclear factor-B (23). Moreover, a recent study has shown that sRAGE modulates the synthesis of CRP (24). An et al (25) reported that circulating sRAGE has a significant negative association with hsCRP in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, serum sRAGE levels in rheumatoid arthritis patients were negatively associated with serum levels of CRP (51). It was also recently described that increased serum CRP together with reduced concentrations of sRAGE appear to be due to elevated TNF-α levels (52). In Il10 null mice, a murine model of colitis, no inflammation in rectosigmoid colon and a decrease in circulating concentrations of TNF-α were observed after treatment with sRAGE (53).…”
Section: O V E M B E R -D E C E M B E R 2 0 1 1 C a L P R O T E C T Imentioning
confidence: 94%